PENGARUH JUMLAH ANGGOTA DAN SIMPANAN ANGGOTA TERHADAP PENINGKATANSISA HASIL USAHA (SHU) PADA PKP-RI (PUSAT KOPERASI PEGAWAI REPUBLIK INDONESIA) PROPINSI SUMATERA BARAT - Ariesta, Ferline; Ansofino, Ansofino; Periadnadi, Periadnadi (Pendidikan Ekonomi, 2013)
ABSTRACTÂ PKP-RI West Sumatra province has been doing some commercial businesses in order to gain the maximum profit or SHU, including the savings and loan and unit sales of the business is expected to contribute greatly to the achievement of the objectives of the cooperative. The purpose of this study is 1) to determine the factors that affect the balance of the (SHU) PKP-RI province of West Sumatra, 2) to examine and analyze the effect of the number of members and the amount of deposits to the balance of the acquisition (SHU) at PKP-RI West Sumatra province, and 3) to test and analyze the variables that have a significant effect between the number of members and the amount of savings to the acquisition of the balance of the PKP-RI in West Sumatra province.The data taken in this study is a financial data from the financial statements of PKP-RI RAT West Sumatra province during the period of 13 years starting from the year 2000 to 2012. The method used is the method of time series. For the formulation of the problem, objectives and hypothesis of the study, the analysis used is the model specification, multiple linear regression analysis, t test, and F test.The research has pointed out that 1) the factors that affect the rest of the results of operations in the PKP-RI West Sumatra province, namely the number of members and member savings, 2) the number of members, member savings and influential sales together to increase PFM - RI SHU Province West Sumatra , and 3) between the number of members, member savings and sales that have a significant influence on the increase in PKP-RI SHU West Sumatra is a members savings, which is obtained t of 4.548.Â Keyword : Number of Members, Member Savings, Member Participation, Sales, and Business Profits